Perinatal death risks of primipara at five District hospitals in Yogyakarta - Haksari EL, Haksari EL (Universitas Gadjah Mada, 2001)
Background: Perinatal death in Indonesia is still high and seems to be difficult to decrease. Beside the characteristics of fetus, neonates, social and environment, there are some maternal characteristics which may increase the risk of perinatal death.Objectives: To identify the risk factors of perinatal death on primipara and multipara.Methods: The data were collected from five district hospitals in Yogyakarta during 1995-1998. The maternal and birth outcome were studied as risk factors of perinatal death.Results: Analysis of multivariate logistic showed primipara aged 5 19 years old had increased Odds ratio (OR) twice as much; prolonged OR stagnated labour and other complications during delivery had increased OR three times as much, haemorrhage had increased OR four times, low birthweight had OR of 3.01 (2.05 -4.43) and preterm had OR 4.15 (2.76-6.16) for perinatal death. Low education and twin of primipara had increased OR twice and three times respectively in univariate analysis. Multipara had increased OR and death of multipara had OR 7.7 (2.0-29.3) for perinatal death.Conclusion: There was a strong association between haemorrhage of delivery, low birth weight and preterm on primipara and perinatal death. Death of multipara had increased OR for perinatal death.Keywords: perinatal death - risk factors - primipara - multipara - district hospital